Analysis of consumer purchase intentions using functional near-infrared spectroscopy(fNIRS): A neuromarketing study on the aesthetic packaging of Korean red ginseng products. - SuJin Bak; Jaeyoung Shin; Daeun Kim; Sungkean Kim (PLoS ONE)
Purpose This study investigates the consumer behavior patterns for Korean red ginseng products using functional near-infrared spectroscopy (fNIRS), a neuroimaging device. By measuring brain activities, we aim to develop neuromarketing techniques and provide insights into consumer purchasing decisions influenced by the aesthetic features of product packaging. Methods Using an fNIRS device, we measured the hemodynamic responses of 50 healthy participants within the prefrontal cortex (PFC) during virtual purchase-response paradigm experiments. These experiments consisted of two scenarios depending on the purpose of purchasing red ginseng products; purchasing for self-consumption and purchasing as gifts for others. These two purchase scenarios were designed to elucidate the relationship between two purchasing scenarios and aesthetic product packaging. Results We observed distinct differences in purchasing behavior between the two scenarios influenced by the packaging of red ginseng products. We found significantly higher prefrontal ∆HbO activation during the gift-giving condition (Task 1) compared to self-consumption (Task 2). Survey results also indicated greater purchase intention (M = 4.35) and great packaging satisfaction (M = 4.18) in Task 1 (p < 0.01) compared to Task 2. No significant differences were observed across gender or age groups. These findings suggest that packaging has a differentiated effect depending on the purchasing context. Conclusions Our findings highlight the need for customized marketing strategies while proposing separate packaging designs for self-consumption and gifts. This study demonstrates the potential of neuromarketing technology based on fNIRS in predicting consumer behavior and improving marketing strategies. Significance Understanding the neural mechanisms of purchasing decisions enables Korean health functional food companies to align their marketing strategies with consumer preferences, thereby enhancing both sales performance and customer satisfaction.